2021
DOI: 10.3390/jcm10040635
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treatment Outcome between Repetitive Transcranial Magnetic Stimulation (rTMS) and Transcutaneous Direct Current Stimulation (tDCS) in Intractable Tinnitus

Abstract: Repetitive transcranial magnetic stimulation (rTMS) and transcutaneous direct current stimulation (tDCS) are non-invasive treatments for chronic tinnitus based on neuromodulation of cortical activity. Both are considered effective, but with heterogeneous results due to lack of established protocols. Because the target groups for both modalities overlap, it is difficult to recommend one of them. We tried to unify the inclusion criteria and treatment schedules to compare the two modalities. The medical charts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Similar to hearing aids, the short duration of this study may not adequately reflect the long-term effect of the treatment. A previous study reported that patients who received rTMS or tDCS demonstrated a continuous reduction in tinnitus loudness and awareness (24). Furthermore, not all patients respond to neuromodulation, and rTMS has been shown to be more effective in women, individually adopted parameters, and comorbid anxiety or depression (25).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to hearing aids, the short duration of this study may not adequately reflect the long-term effect of the treatment. A previous study reported that patients who received rTMS or tDCS demonstrated a continuous reduction in tinnitus loudness and awareness (24). Furthermore, not all patients respond to neuromodulation, and rTMS has been shown to be more effective in women, individually adopted parameters, and comorbid anxiety or depression (25).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 18 studies involving DLPFC were found. 48 , 56 72 Vanneste et al 60 showed that single bilateral DLPFC stimulation significantly inhibited tinnitus loudness and annoyance. Faber et al 58 reported that multiple sessions of tDCS of DLPFC only yielded benefits in improving tinnitus distress, while Shekhawat and Vanneste 66 found that DLPFC was effective for improving tinnitus loudness.…”
Section: Dorsolateral Prefrontal Cortexmentioning
confidence: 99%
“…One study compared the treatment outcomes between rTMS and tDCS and revealed comparable results in reducing tinnitus in terms of the changes in Tinnitus Handicap Inventory (THI) scores, Numeric Rating Scale (NRS) scores, and duration [21]. Further studies suggest that combining neuromodulation techniques (rTMS + tDCS) improves the treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%